Impact of different anesthetic approaches on the outcomes of temporomandibular joint arthrocentesis: a systematic review - Silva, Felipe Medeiros da; Serrano, Rafael Verardi; Sato, Fábio Ricardo Loureiro [UNESP]; Moraes, Luís Otávio Carvalho de; Campos, Luana; Palma, Luiz Felipe (Springer Nature, 2022)
Purpose: To assess the impact of different types of anesthesia on the outcomes of arthrocentesis of the TMJ. Methods: Electronic databases were searched to identify peer-reviewed studies, followed by reference list search and further hand-searching. Randomized clinical trials and controlled studies were considered for inclusion when comparing at least two anesthetic approaches. The risk of bias was assessed using the Cochrane risk of bias tool. Results: Of a total of 506 potentially eligible studies, only a randomized controlled clinical trial and an observational study were included. The former compared some outcomes of arthrocentesis under local and general anesthesia and the latter under sedation and general anesthesia. Moreover, both studies were judged as “high risk of bias.” Conclusions: In general, there appears to be a slight trend toward better outcomes of arthrocentesis for internal TMJ derangements (Wilkes grades I to III) when performed under general anesthesia; however, given that the available evidence is remarkably limited and a high risk of bias was detected within the included studies, a definitive statement cannot be made.
Keywords: Anesthesia; Maxillofacial surgery; Temporomandibular joint; Temporomandibular joint arthrocentesis; Temporomandibular joint disorders